2019
DOI: 10.1186/s12889-019-6691-7
|View full text |Cite
|
Sign up to set email alerts
|

Understanding factors influencing linkage to HIV care in a rural setting, Mbeya, Tanzania: qualitative findings of a mixed methods study

Abstract: Background In remote rural Tanzania, the rate of linkage into HIV care was estimated at 28% in 2014. This study explored facilitators and barriers to linkage to HIV care at individual/patient, health care provider, health system, and contextual levels to inform eventual design of interventions to improve linkage to HIV care. Methods We conducted a descriptive qualitative study nested in a cohort study of 1012 newly diagnosed HIV-positive individuals in Mbeya region betw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

11
53
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(65 citation statements)
references
References 29 publications
(24 reference statements)
11
53
1
Order By: Relevance
“…Many factors have been associated with retention in care, including individual level factors (feeling sick and having symptoms, moral support from relatives, fear of stigma, misunderstanding about importance of care, financial constraints), provider level (negative healthcare provider attitudes, abusive language), health system level (overcrowding, inadequate resources), and contextual factors (proximity to clinic) [ 15 17 ]. Prior non-retention and tracing studies for HIV care to find patients who have been lost to follow-up have shown an inverse association between poverty and attendance at clinic [ 17 , 29 , 30 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Many factors have been associated with retention in care, including individual level factors (feeling sick and having symptoms, moral support from relatives, fear of stigma, misunderstanding about importance of care, financial constraints), provider level (negative healthcare provider attitudes, abusive language), health system level (overcrowding, inadequate resources), and contextual factors (proximity to clinic) [ 15 17 ]. Prior non-retention and tracing studies for HIV care to find patients who have been lost to follow-up have shown an inverse association between poverty and attendance at clinic [ 17 , 29 , 30 ].…”
Section: Discussionmentioning
confidence: 99%
“…3 months) with at least one visit, and gaps between visits [ 12 ]. Various patient and healthcare system factors have been associated with retention in care, including degree of symptoms, financial constraints, distance from the clinic, decreased wait times, and improved patient satisfaction [ 15 17 ]. While routinely measured in the HIV/AIDS care continuum literature and linked to viral loads [ 18 , 19 ], medication adherence, and mortality [ 20 , 21 ], visit adherence and its predictors have not been routinely examined for chronic disease care in LMIC.…”
Section: Introductionmentioning
confidence: 99%
“…Variation of the finding in the later study might be due to their good experience in implementing the service since it was an area in which Option B + PMTCT first piloted internationally [29]. Identified barriers for process related factors during an interview were poor service adherence to service standards, work load, and prolonged waiting time which were similarly reported from [30,34,35]. This process related factors had serious implications in compromising the overall quality of care currently aspired in 2020 [10,19].…”
Section: Discussionmentioning
confidence: 84%
“…[ 19 ] Tanzania's health communication research in the rural areas studied the influence of HIV care and examined the reaction of HIV prevention methods done in those areas. [ 20 21 ] Other studies focused on the risks associated with sexual relationship between homosexual men and its implications for HIV, the importance of parental communication in supporting HIV patients, and the significance of social networks in increasing the willingness for HIV self-testing. [ 22 23 24 25 ]…”
Section: Discussionmentioning
confidence: 99%